Notes on taxonomy, biology and fishery of Ucides occidentalis (Brachyura: Ocypodidae) with emphasis in the Gulf of Guayaquil, Ecuador - Zambrano, René (2018)
Scientific information on Ucides occidentalis is scarce, and part of these studies have not adequate diffusion, this situation restricts the availability of knowledge about this commercial species. In this work, on the one hand, diverse studies on U. occidentalis are reviewed, and on the other, information obtained from direct observations made since 2011 to 2014 in the Gulf of Guayaquil mangroves, is presented. Notes on changes in the taxonomy of U. occidentalis, its biology, ecological and fishery characteristics are presented. Characteristics to fishing interest such as density data and reproduction periods are discussed. By last, it is discussed the management of fisheries of U. occidentalis in the Gulf of Guayaquil, because in recent decades, U. occidentalis has evidenced a decrease in the landing levels and at the same time, an increase in the average commercial size; this suggest that both factors should be considered in the evaluation of stock, and thereby to have a better approximation on the population status of the resource.